2012
DOI: 10.1002/ctpp.201200031
|View full text |Cite
|
Sign up to set email alerts
|

Optical Emission of Molecular Hydrogen in a Recombining Hydrogen Plasma

Abstract: We observed optical emission of molecular hydrogen in a recombining hydrogen plasma with an electron temperature of 0.1 eV and an electron density of 3 × 10 12 cm −3 . The optical emission intensities of molecular hydrogen in the recombining plasma were roughly 10%-45% of those in an ionizing plasma with an electron temperature of 4 eV. The ratio was greater for a transition line originated from an excited state with a larger vibrational quantum number. Because of the low electron temperature of 0.1 eV, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…When the rf power was higher than 2.5 kW, we observed the production of a recombining plasma in the downstream region of the plasma column. 18,19) As shown in Fig. 1, the position of the orifice was adjusted in the transition region between the ionizing and recombining plasmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the rf power was higher than 2.5 kW, we observed the production of a recombining plasma in the downstream region of the plasma column. 18,19) As shown in Fig. 1, the position of the orifice was adjusted in the transition region between the ionizing and recombining plasmas.…”
mentioning
confidence: 99%
“…The optical emission spectrum was composed of the Balmer series of atomic hydrogen, in which the upper energy states of the transition lines had principal quantum numbers of up to 12. 18,19) We evaluated the absolute population densities of the upper energy states by dividing the emission coefficients by the transition probabilities of the corresponding Balmer lines. It was found that the distribution of the population densities of the energy states with principal quantum numbers of n ≥ 5 was fitted by the Saha-Boltzmann equation, indicating that the energy states with n ≥ 5 were in local thermodynamic equilibrium.…”
mentioning
confidence: 99%